PERAN BAHASA ARAB DALAM PENGEMBANGAN ILMU DAN PERADABAN ISLAM - Muhbib Abdul Wahab (Syarif Hidayatullah State Islamic University of Jakarta, 2014)
This study aims to clarify the role of the Arabic language in advancing science and Islamic civilization through a library study of the history of the Arab ic language a long the ages. The approach used to analyze the data of Arabic language development is hist orical approach combined with content analysis approach. The study has come to the conclusion that there are βive important roles of Arabic language. Firstly, it served as the language of the union among the people and the Arab tribes. Secondly, Arabic preserved the richness of local Arabic cultures through all times. Thirdly, Arabic used as a media for educational and scientiβic study, possitioning it as the language of science and technology. Fourthly, Arabic is as a tool of communication among the people and tribes and generations. Fifthly, Arabic is accepted as a standardized language for Islamic knowledge and modern sciences.   DOI: 10.15408/a.v1i1.1127